Protective hybrid coating containing silver, copper and zinc cations effective against human immunodeficiency virus and other enveloped viruses - Hodek, Jan; Zajícová, Veronika; Lovětinská-Šlamborová, Irena; Stibor, Ivan; Müllerová, Jana; Weber, Jan (BMC microbiology, 2016)
BACKGROUND: Healthcare-acquired infections by pathogenic microorganisms including viruses represent significant health concern worldwide. Next to direct transmission from person-to-person also indirect transmission from contaminated surfaces is well documented and important route of infections. Here, we tested antiviral properties of hybrid coating containing silver, copper and zinc cations that was previously shown to be effective against pathogenic bacteria including methicillin-resistant Staphylococcus aureus. Hybrid coatings containing silver, copper and zinc cations were prepared through radical polymerization via sol-gel method and applied on glass slides or into the wells of polymethylmethacrylate plates. A 10 μl droplet of several viruses such as human immunodeficiency virus type 1 (HIV-1), influenza, dengue virus, herpes simplex virus, and coxsackievirus was added to coated and uncoated slides or plates, incubated usually from 5 to 240 min and followed by titer determination of recovered virus. RESULTS: Scanning electron microscopy analysis showed better adhesion of coatings on glass surfaces, which resulted in 99.5-100 % HIV-1 titer reduction (3.1 ± 0.8 log10TCID50, n = 3) already after 20 min of exposure to coatings, than on coated polymethylmethacrylate plates with 75-100 % (1.7 ± 1.1 log10TCID50, n = 3) and 98-100 % (2.3 ± 0.5 log10TCID50, n = 3) HIV-1 titer reduction after 20 and 120 min of exposure, respectively. Slower virucidal kinetics was observed with other enveloped viruses, where 240 min exposure to coated slides lead to 97 % (dengue), 100 % (herpes simplex) and 77 % (influenza) reduction in virus titers. Interestingly, only marginal reduction in viral titer after 240 min of exposure was noticed for non-enveloped coxsackie B3 virus. CONCLUSIONS: Our hybrid coatings showed virucidal activity against HIV and other enveloped viruses thus providing further findings towards development of broad-spectrum antimicrobial coating suitable for surfaces in healthcare settings.
Keywords: Equipment and Supplies, Hospital; kationty; Humans; HIV infekce; vybavení a zásoby nemocnice; Copper; HIV Infections; Hybrid coating; Cations; Zinc; lidé; zinek; Silver; Virucidal effect; infekce spojené se zdravotní péčí; kontaminace zdravotnického vybavení; měď; antivirové látky; stříbro; HIV; Viruses; Antiviral Agents; Enveloped viruses; viry; HIV-1; Equipment Contamination; Cross Infection